SPATIAL THINKING MAHASISWA DALAM PEMBELAJARAN ANATOMI TUMBUHAN BERBASIS FRAMING - Ermayanti, Ermayanti; Rustaman, Nuryani Y; Rahmat, Adi (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
A study to investigate the role of framing in plant anatomy course was conducted to facilitate spatial thinking of prospective teachers. A number of Biology Education students in one state university in South Sumatra was involved in this study (n=35). Data on spatial thinking ability was collected through the usage of test developed based on Kosslyn framework and observation sheet been validated by expert judgment. Pre-test and post-test results were analyzed by using percentage and N-Gain for each spatial thinking indicator (generating representation, maintaining and managing representation in working memory, scanning the representation and transforming the representation). The study resulted in that there is improvement of studentsâ spatial thinking with N-gain 46.1 (moderate category) after having experience through framing based learning instruction. The highest percentage of studentsâ spatial thinking is generating representation (86.4) and the lowest is transforming representation (50.0). Research finding shows that framing had not fully framed studentsâ maintaining and managing representation, as well as transforming representation. In order to increase studentsâ spatial thinking, it is needed revision on framing dynamics.